Comparison of COVID-19 and Lung Cancer via Reactive Oxygen Species Signaling - Zhu, Zilan; Zheng, Ziyi; Liu, Jian (Frontiers in Oncology, 2021)
COVID-19 and lung cancer are two severe pulmonary diseases that cause millions of deaths globally each year. Understanding the dysregulated signaling pathways between them can benefit treating the related patients. Recent studies suggest the critical role of reactive oxygen species (ROS) in both diseases, indicating an interplay between them. Here we reviewed references showing that ROS and ROS-associated signaling pathways, specifically via NRF2, HIF-1, and Nf-κB pathways, may bridge mutual impact between COVID-19 and lung cancer. As expected, typical ROS-associated inflammation pathways (HIF-1 and Nf-κB) are activated in both diseases. The activation of both pathways in immune cells leads to an overloading immune response and exacerbates inflammation in COVID-19. In lung cancer, HIF-1 activation facilitates immune escape, while Nf-κB activation in T cells suppresses tumor growth. However, the altered NRF2 pathway show opposite trends between them, NRF2 pathways exert immunosuppressive effects in both diseases, as it represses the immune response in COVID-19 patients while facilitates the immune escape of tumor cells. Furthermore, we summarized the therapeutic targets (e.g., phytochemicals) on these ROS pathways. In sum, our review focus on the understanding of ROS Signaling in COVID-19 and lung cancer, showing that modulating ROS signaling pathways may alleviate the potentially mutual impacts between COVID-19 and lung cancer patients.